Purchase order of floor finishing with non- shrink repair mortar at the footsteps of the opening for BRACU new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Safe Constructions Solutions for floor finishing with non- shrink repair mortar at the footsteps of the opening for BRACU new campus project.